Perfluoroalkyl substances (PFAS) in drinking water and risk for polycystic ovarian syndrome, uterine leiomyoma, and endometriosis: A Swedish cohort study - Sofia Hammarstrand; Kristina Jakobsson; Eva Andersson; Yiyi Xu; Ying Li; Matts Olovsson; Eva M Andersson (Environment International, 2021)
Background: Perfluorinated substances (PFAS) are chemicals with endocrine disruptive properties that may interfere with the female reproductive system. However, few studies have explored the association between benign gynecological diseases and high PFAS exposure. Objectives: The aim of this study was to investigate the possible associations between PFAS exposure and subsequent diagnosis of polycystic ovarian syndrome (PCOS), uterine leiomyoma (fibroids), and endometriosis in a cohort exposed to PFAS through drinking water. Material and methods: In 2013, high levels (with sum of PFAS above 10,000 ng/L), dominated by perfluorooctanesulfonic acid (PFOS) and perfluorohexane sulfonic acid (PFHxS), were found in the drinking water from one of the two waterworks in Ronneby, Sweden. The contamination came from firefighting foams used at a nearby airfield. Females of all ages (n = 29,106) who had ever resided in the municipality between 1985 and 2013 formed a cohort. Individual exposure was assessed based on municipality waterworks distribution data linked to annual residential address data; 27% of the females had ever lived at an address with PFAS-contaminated water. Gynecological health outcomes were retrieved from the Swedish National Patient Register. The Cox proportional hazards model was used to estimate the association between exposure and each diagnosis. Results: There were in all 161 cases of PCOS, 1,122 cases of uterine leiomyoma, and 373 cases of endometriosis. In women aged 20–50 years (n = 18,503), those with the highest estimated PFAS exposure had increased hazard ratios (HR) for PCOS (HR = 2.18; 95% confidence interval (CI) 1.43, 3.34) and uterine leiomyoma (HR = 1.28; 95% CI 0.95, 1.74). No increased HR for endometriosis was found (HR = 0.74; 95% CI 0.42, 1.29). Conclusions: Exposure to high levels of PFAS in drinking water was associated with increased risk of PCOS and possibly uterine leiomyoma, but not endometriosis. The findings for PCOS are consistent with prior studies reporting positive associations between PCOS and PFAS exposure at background levels.